Pengembangan Model Inclusive QFaA dalam Pendidikan Islam untuk Siswa dengan Pembelajaran Bagi Disabilitas di Malaysia - Norfishah Mat Rabi; Nor Hasnida Che Md Ghazali; Norwaliza Abdul Wahab; Nor Aizal Akmal Rohaizad (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
AbstractIslamic Education is a compulsory subject in National Curriculum in Malaysia. This subject is taught to all Muslim student in primary and secondary school including a student with a learning disability (SLD). SLD was identified having a problem in the learning process, and they need extra effort to learn. This study is conducted to develop a model of teaching reciting Al-Quran, prayer, and Arabic in Islamic Education for SLD. The objective of the study was covering identification of screening items, timetable planning, teacher’s qualifications, teaching aids, and assessment methods. The sample consisted of 15 Special Education teachers and 15 mainstream teachers from a secondary school in Perak. This case study was involving focus group interview and analysis of documents. The analysis of data based on qualitative method and findings reported descriptively using percentage values. The findings showed that Special Education and mainstreams teacher supported the construct to be used in the development of the QFaA Inclusive Model with different views on the elements for screening items, timetable planning, teaching aids, assessment methods, and teacher’s qualifications. This model can be a guide in providing an inclusive model on teaching and learning of Al-Quran, prayers, and Arabic to students with learning disabilities in an inclusive program. The QFaA Inclusive Model will provide an alternative model for teachers and the school to modify the current model to be in line with the needs of the students. Keywords: Inclusive Model, Islamic Education, Learning Disability. AbstrakPendidikan Islam merupakan mata kuliah wajib di Kurikulum Nasional di Malaysia. Subjek ini diajarkan kepada semua siswa Muslim di sekolah dasar dan menengah termasuk siswa dengan ketidakmampuan belajar (SLD). SLD diidentifikasi memiliki masalah dalam proses belajar dan mereka membutuhkan usaha ekstra untuk belajar. Penelitian ini dilakukan untuk mengembangkan model pengajaran membaca Al-Quran, sholat dan bahasa Arab dalam Pendidikan Islam untuk SLD. Tujuan penelitian ini meliputi identifikasi item skrining, perencanaan jadwal, kualifikasi guru, alat peraga, dan metode penilaian. Sampel terdiri dari 15 guru Pendidikan Khusus dan 15 guru utama dari sekolah menengah di Perak. Studi kasus ini melibatkan wawancara kelompok fokus dan analisis dokumen. Analisis data berdasarkan metode kualitatif dan temuan dilaporkan secara deskriptif dengan menggunakan nilai persentase. Temuan menunjukkan bahwa guru Pendidikan Khusus dan arus utama mendukung pembangunan tersebut untuk digunakan dalam pengembangan Model Inklusif QFaA dengan pandangan yang berbeda mengenai elemen untuk item skrining, perencanaan jadwal, alat bantu pengajaran, metode penilaian, dan kualifikasi guru. Model ini bisa menjadi panduan dalam menyediakan model inklusif tentang pengajaran dan pembelajaran Al-Quran, doa dan bahasa Arab kepada siswa dengan ketidakmampuan belajar dalam program inklusif. QFaA Inclusive Model akan menyediakan model alternatif bagi guru dan sekolah untuk memodifikasi model saat ini agar sesuai dengan kebutuhan siswa. Kata Kunci: Model Inklusif, Pendidikan Islam, Ketidakmampuan Belajar.